Composição das ceras cuticulares de maçãs ‘Cripps Pink’, ‘Maxi Gala’ e ‘Elstar’: consequências no metabolismo e qualidade do fruto após o armazenamento - Klein, Bruna (2021)
Apple cultivation has a restricted harvest to a few months of the year, resulting in periods of high and low supply of fruit. Due to its seasonality, storage is an important factor in offering quality fruit in the off-season. As an alternative to controlled atmosphere (CA) storage, new storage technologies have been developed, that use techniques capable of safely reducing partial O2 pressure by monitoring the lowest O2 limit (LOL), associated with fruit metabolism. These storage systems are known as dynamic controlled atmosphere (DCA). DCA systems already show advantages in maintaining post-harvest quality of fruit for a longer period of time. Recent studies have shown important aspects in relation to the cuticle of the epidermis and the post-harvest performance of the fruit. However, the assessment of cuticular composition associated with DCA techniques has not been reported to date. In view of this, in the present work, three scientific articles were developed with the objectives of: [1] Evaluate the changes in the concentration and chemical composition of ‘Cripps Pink’ apple peel wax after storage under CA, DCA-CF and DCA-RQ conditions and the relationship of these changes with metabolism, decay incidence, and greasiness development in the skin of the fruit; [2] Evaluate the effects of the interaction between the DCA (CF and RQ) and 1-MCP methods on the concentration, chemical composition of the wax and on the general quality of ‘Maxi Gala’ apples after storage; [3] evaluate the concentration and chemical composition of waxes from ‘Elstar’ apple peels stored under CA, DCA-CF, DCA-RQ and compare with DCA-CD (a new DCA method, based on the CO2 production of fruit) and relate the changes with the metabolism, decay incidence, and general quality of the fruit. DCA storage of ‘Cripps Pink’ apples increased the total wax content over the shelf life, although apples stored in DCA-RQ did not develop greasiness in the epidermis, which is considered a physiological storage disorder. Fatty esters, ursolic acid, oleanolic acid and, palmitic acid were correlated with greater greasiness in the epidermis. DCA-RQ1.3 showed the lowest respiratory rate, showing a lower metabolism and corroborating with the greater number of healthy fruit and consequently a better storage condition. Storage with less pO2, as in DCA-RQ, may have favored adaptation mechanisms against low pO2, inducing the formation of compounds such as 10-nonacosanol and octacosanol, which gives the cuticle a crystalline structure. For ‘Maxi Gala’ apples, the application of 1-MCP was effective in reducing ethylene production in CA, although DCA, especially DCA-RQ, has also been shown to reduce the overall metabolism of the fruit. As for cuticular wax, the storage atmospheres and treatment with 1-MCP did not influence the total wax content. The wax compositions of the apples stored in DCA were similar when 1-MCP was applied. However, 1-MCP may be associated with a suppression in alkane biosynthesis and, consequently, greater loss of mass in the fruit stored in DCA. For ‘Elstar’ apples, storage under DCA-RQ and DCA-CD or CA+1-MCP reduced ethylene production and delayed fruit ripening. DCA-RQ1.5 resulted in a lower decay incidence and was associated with a greater accumulation of compounds of anaerobic metabolism. ACD-QR and -DC resulted in greener (ºHue) and more opaque (C *) fruits when compared, mainly to AC, were the treatments with the lowest wax levels and showed similarity in the chemical composition of the wax. In general, changes in wax composition showed significant variations related to storage and cultivar specificities. However, the understanding of the relationship between post-harvest characteristics and specific chemical components is still preliminary. New studies may lead to a better understanding of the mechanisms underlying the wide variation in the post-harvest potential of apples related to the cuticular layer.